Environmental Impact of Limestone Mining Using A Life Cycle Assessment Method - Murodif, Atfal; Fauzi, Anas Miftah; Erizal; Karlinasari, Lina (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2025)
The extraction of limestone for cement production can adversely affect the environment. An inquiry is underway to examine the environmental ramifications of limestone mining to formulate strategies to mitigate these effects. This study aims to assess the ecological impact indicators of the limestone mining process by utilizing the LCA method based on CML-IAbaseline data from the openLCA software. The results indicate that crushing is a significant area of focus, contributing the most extensive value. The ratio of Ammonium Nitrate to diesel oil in adherence to guidelines is 94.5 to 5.5%. Particular emphasis is placed on assessing raw materials, especially during the loading and hauling stages. In conclusion, the research findings reveal environmental impact indicators with standardized values, such as Abiotic Depletion, Abiotic Depletion of Fossil Fuels, Acidification, Eutrophication of Freshwater Aquatic Ecotoxicity, Global Warming 100a, Human Toxicity, Marine Aquatic Ecotoxicity, Ozone Layer Depletion, Photochemical Oxidation, and Terrestrial Ecotoxicity.